Cybercrime: a theoretical overview of the growing digital threat : in the framework of the project ‘The development of the observatory function of the European Centre of Expertise on Crime Prevention within the EUCPN’ -EUCPN Secretariat, February 2015, Brussels - Verleysen, Cindy (Theoretical paper, 2016)
This theoretical paper is published by the EUCPN Secretariat in connection with the theme of the Luxembourgian presidency which was cybercrime. Cybercrime is a global definition which characterizes many different criminal forms committed in the virtual world. This means the phenomenon covers a very wide scope of activities. This theoretical paper is written as an overview to help understand the definition of cybercrime and its forms. We concentrate on the variety of consequences as a result of the phenomenon. Moreover, this paper also has attention to the current European law and legislative actions against cybercrime.